Complex Polyploids: Origins, Genomic Composition, and Role of Introgressed Alleles - Leal, J Luis; Milesi, Pascal; Hodková, Eva; Zhou, Qiujie; James, Jennifer; Eklund, D Magnus; Pyhäjärvi, Tanja; Salojärvi, Jarkko; Lascoux, Martin (Systematic biology, 2024)
Introgression allows polyploid species to acquire new genomic content from diploid progenitors or from other unrelated diploid or polyploid lineages, contributing to genetic diversity and facilitating adaptive allele discovery. In some cases, high levels of introgression elicit the replacement of large numbers of alleles inherited from the polyploid's ancestral species, profoundly reshaping the polyploid's genomic composition. In such complex polyploids, it is often difficult to determine which taxa were the progenitor species and which taxa provided additional introgressive blocks through subsequent hybridization. Here, we use population-level genomic data to reconstruct the phylogenetic history of Betula pubescens (downy birch), a tetraploid species often assumed to be of allopolyploid origin and which is known to hybridize with at least four other birch species. This was achieved by modeling polyploidization and introgression events under the multispecies coalescent and then using an approximate Bayesian computation rejection algorithm to evaluate and compare competing polyploidization models. We provide evidence that B. pubescens is the outcome of an autoploid genome doubling event in the common ancestor of B. pendula and its extant sister species, B. platyphylla, that took place approximately 178,000-188,000 generations ago. Extensive hybridization with B. pendula, B. nana, and B. humilis followed in the aftermath of autopolyploidization, with the relative contribution of each of these species to the B. pubescens genome varying markedly across the species' range. Functional analysis of B. pubescens loci containing alleles introgressed from B. nana identified multiple genes involved in climate adaptation, while loci containing alleles derived from B. humilis revealed several genes involved in the regulation of meiotic stability and pollen viability in plant species.
Keywords: homoeologs; Genome, Plant; genom rostlinný; autopolyploidy; introgressive hybridization; fylogeneze; Phylogeny; Betula; bříza; Allopolyploidy; polyploid phylogenetics; genomic polarization; genová introgrese; Hybridization, Genetic; hybridizace genetická; Polyploidy; reticulate evolution; Alleles; gene flow; alely; Genetic Introgression; polyploidization simulation; interploidal; polyploidie